Osteoclasts Derive Predominantly from Bone Marrow-Resident CX(3)CR1(+) Precursor Cells in Homeostasis While Circulating CX(3)CR1(+) Cells Contribute to Osteoclast Development During Fracture Repair - Novak, Sanja (J Immunol, 2020)
Osteoclasts (OC) originate from either bone marrow (BM)-resident or circulating myeloid OC progenitors (OCP), expressing the receptor CX(3)CR1. Multiple lines of evidence argue that OCP in homeostasis and inflammation differ. We investigated the relative contributions of bone marrow-resident and circulating OCP to osteoclastogenesis during homeostasis and fracture repair. Using CX(3)CR1-EGFP/TRAP tdTomato mice we found CX(3)CR1 expression in mononuclear cells but not in multinucleated TRAP(+) OC. However, CX(3)CR1-expressing cells generated TRAP(+) OC on bone within 5 days in CX(3)CR1CreERT2/Ai14 tdTomato reporter mice. To define the role that circulating cells play in osteoclastogenesis during homeostasis, we parabiosed TRAP tdTomato mice (CD45.2) on a C57BL/6 background with wild type (WT) mice (CD45.1). Flow cytometry (CD45.1/.2) demonstrated abundant blood cell mixing between parabionts after 2 weeks. At 4 weeks there were numerous tdTomato(+) OC in the femurs of TRAP tdTomato mice but almost none in WT mice. Similarly, cultured BM stimulated to form OC demonstrated multiple fluorescent OC in cell cultures from TRAP tdTomato mice but not from WT mice. Finally, flow cytometry confirmed low - level engraftment of BM cells between parabionts but significant engraftment in the spleens. In contrast, during fracture repair, we found that circulating CX(3)CR1(+) cells migrated to bone, lost expression of CX(3)CR1 and became OC. These data demonstrate that OCP but not mature OC express CX(3)CR1 during both homeostasis and fracture repair. We conclude that in homeostasis mature OC derive predominantly from bone marrow-resident OCP, while during fracture repair, circulating CX(3)CR1(+) cells can become OC.